MINERALOGY OF CHROMITITE, BULQIZA ULTRAMAFIC MASSIF, ALBANIAN OPHIOLITIC COMPLEX - Çina, A. (Bulletin of the Geological Society of Greece, 2010)
Ultramafic massif of Bulqiza belongs to Eastern Jurassic Albanian ophiolite belt of IAT-BSV- type. This massif is the most important chromite-bearing ore. The mantle ultramafics have extremely refractory nature. This is due to the high partial fusion of upper mantle which is depleted in CaO and Al2 O3 . The chromitite is situated to different parts of ultramafic pile, from bottom Cpx harzburgites up to massive dunites and cumulate ultramafic but the mainly chromite potential belongs to mantle harzburgite –dunite level and to transition dunites partly. The chromite is chiefly of Cr-rich metallurgical type. The atomic ratios of chromite , Fo of olivine and some physical properties of them vary according to the chromitite setting and reflects the evolution of Ol-Sp equilibrium process depended of the chromite concentration, from baren dunitic lenses towards dunite envelops of the ore bodies and the interstitial and inclusions of olivine within chromite grains. Two particular chromite deposits are the Bulqiza- Batra tabular folded ore body and Shkalla, pencil –like ore body.